2017
DOI: 10.5007/2175-8026.2017v70n3p227
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining L2 accent: How much can personality explain?

Abstract: Previous studies have shown that learners’ individual differences (e.g., motivation, age) can impact second language learners’ pronunciation. This study focused on one individual difference that has received relatively little attention, namely personality, and sought to determine to what extent personality accounts for learners’ L2 accent during quasispontaneous and unplanned speech. Fifty-one English-speaking learners of Spanish performed a speaking task that was scored for degree of L2 accentedness. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the same study showed that empathy was a significant correlate of accurate pronunciation (r=.26, p=.024). Another researcher investigating the link between the Big Five personality traits and pronunciation is Zárate-Sández (2017). This time, the data were gathered among 51 highly advanced American learners of Spanish, whose level of accentedness was rated with the use a picture description task and a 6-point accentedness Likert scale.…”
Section: Personality and Fl Pronunciation-related Attainmentreview Of...mentioning
confidence: 99%
“…Moreover, the same study showed that empathy was a significant correlate of accurate pronunciation (r=.26, p=.024). Another researcher investigating the link between the Big Five personality traits and pronunciation is Zárate-Sández (2017). This time, the data were gathered among 51 highly advanced American learners of Spanish, whose level of accentedness was rated with the use a picture description task and a 6-point accentedness Likert scale.…”
Section: Personality and Fl Pronunciation-related Attainmentreview Of...mentioning
confidence: 99%